Mapping approach for examining waste management within construction sites - Sim, Lee Gaik (2005)
In light of increased awareness on environmental impacts from construction wastes, waste management has become an important factor in construction project management. Various waste managements have been developed by researchers to manage construction wastes. Nevertheless, less attention is given towards the management of waste handling processes on construction sites such as waste sorting and waste transport. In fact, proper flow of these processes could improve waste management effectiveness. The aim of the study is to examine waste handling process during construction through the mapping of ten project sites in Melaka using the free-flow mapping presentation technique. This will lead to the development of a proposed waste management mapping model (WMMM), which incorporates the good operations embodied in the existing practices and also the outcomes of interviews with the project proponents. The WMMM could serve as a tool assisting in planning waste management procedures as well as a vehicle for comparing waste management practices among construction sites; thus, weaknesses and good practices could be identified and improvement measures may be implemented accordingly. Personal interviews with questionnaires and on site observations were administered for data collection. Analysis was performed on results tabulated in matrix table with interpretation assisted by statistical computations. Qualitative approach was of dominant where comparative evaluation was extensively performed on the waste management practices between these ten sites. Findings revealed that the advantages of waste handling practices outnumbered the weaknesses. The WMMM was proposed based on guidelines derived from the analysis which took into account factors pertaining to cost, environmental protection and time in waste handling management. It was suggested that the proposed WMMM could be incorporated into the Environmental Impact Assessment (EIA) report to assist waste management planning. Overall, the findings of the study have contributed to the basic understanding of the waste management practices within construction sites in Malaysia